DESAIN ARSITEKTUR APLIKASI QR CODE SEBAGAI ANTI PHISHING SERANGAN QR CODE - Slamet Slamet (SPIRIT, 2023)
QR Codes are very vulnerable to falsification because it is difficult to distinguish the original QR Code from a fake QR Code. Because of this vulnerability, the scanning process on fake QR Codes can direct users to dangerous sites with important information or data from the user. To assess QR Code security vulnerabilities and actions using a secure Application-based QR Code Architecture as Anti Phishing against QR Code attacks using hash functions and digital signatures. In experiments simulated attack types to malicious QR codes that redirect users to phishing sites. The real URL is disguised into the QR Code, where the user does not suspect, the URL is redirected to the fake site. As a result, intruders can easily use QR codes as vectors for phishing attacks targeted at smartphone users, even if they are using a browser that has security features.Â